Efektivitas Komik Sebagai Media Pembelajaran Matematika - Moh Abdul Shomad; Susi Rahayu (IKIP PGRI Bojonegoro, 2022)
Abstract: The purpose of this study was to determine the effectiveness of using comics as a learning medium in mathematics. This research method is the SLR (Systematic Literature Review) method. This method includes identifying, reviewing, evaluating and interpreting all available research in the form of journals, articles and others. Based on the results of the study, it was found that comics were an interesting, simple, and easy-to-understand learning medium for students so as to facilitate the teaching and learning process and increase learning motivation and improve student learning outcomes.Keywords:comik: Learning media: Mathematics